2008
DOI: 10.1007/s10616-008-9148-x
|View full text |Cite
|
Sign up to set email alerts
|

Restraint stress up-regulates expression of zinc transporter Zip14 mRNA in mouse liver

Abstract: The zinc concentration in the liver was significantly higher in mice at 12 h after the onset of restraint stress than that without stress. The IL-6 protein level in the serum was transiently elevated at 3 h after the onset of restraint stress, and the IL-6-responsive zinc transporter Zip14 mRNA in the liver was expressed markedly at 6 h. These results suggest that Zip14 plays a major role in the mechanism responsible for accumulation of zinc in the liver under restraint stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Overall, circulating zinc concentrations were reduced whilst liver zinc was significantly higher in all stress groups compared to unstressed controls. These results agree with previous studies which employed both acute and chronic stress models in addition to in vitro studies using primary hepatocytes treated with synthetic glucocorticoids [ 27 , 55 , 56 , 57 ]. Furthermore, zinc deficiency has been observed in individuals suffering from anxiety and depression, whilst a zinc-deficient diet has been shown to influence the severity of depressive symptoms in women but not men [ 58 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, circulating zinc concentrations were reduced whilst liver zinc was significantly higher in all stress groups compared to unstressed controls. These results agree with previous studies which employed both acute and chronic stress models in addition to in vitro studies using primary hepatocytes treated with synthetic glucocorticoids [ 27 , 55 , 56 , 57 ]. Furthermore, zinc deficiency has been observed in individuals suffering from anxiety and depression, whilst a zinc-deficient diet has been shown to influence the severity of depressive symptoms in women but not men [ 58 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the zinc exporter ZnT1 showed an initial increase in mRNA levels before becoming significantly downregulated following repeated stress exposure which could facilitate hepatic zinc sequestration in these longer stress durations. Zinc accumulation by the liver is also supported by the significant increase in the zinc importer, Zip14, which is comparable with previous studies [ 27 , 56 ]. Furthermore, Liuzzi and colleagues [ 66 ] have shown that hepatic Zip14 is highly responsive to inflammatory cytokines including interleukin-6 and is responsible for producing the hypozincemia in circulation observed in an acute phase response.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Markers that show stress at an early stage will therefore be useful for diagnostic purposes. Researchers have attempted to establish methods to evaluate both pathological and physiological stress using biochemical markers, such as the concentrations of ACTH, catecholamine, galectin-1 prolactin, leptin, chromogranin A, and cortisol in the peripheral blood, saliva or urine (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Some experiments showed that the zinc concentration in the liver was significantly higher in mice at 12 h after the onset of restraint stress than that without stress. The interleukin-6 (IL-6) protein level in the serum was transiently elevated at 3 h after the onset of restraint stress, and the IL-6-responsive zinc transporter ZRT/IRT-like Protein 14 (ZIP14) mRNA in the liver was expressed markedly at 6 h [ 19 ]. These results suggest that ZIP14 plays a major role in the mechanism responsible for accumulation of zinc in the liver under restraint stress.…”
Section: Introductionmentioning
confidence: 99%